Rash after treatment with anistreplase. Issue 4 (October 1990) - Burrows, N; Jones, R R
Abstract : A palpable purpura developed on the legs and lower abdomen of a woman of 54 five days after she was treated with anistreplase anisoylated plasminogen streptokinase activator complex (APSAC) for an acute myocardial infarction. Histological examination of a skin biopsy specimen taken 6 days after treatment showed leucocytoclastic vasculitis. The rash resolved within two weeks and there were no other complications.